2007
DOI: 10.1016/j.ceb.2007.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Catenins: playing both sides of the synapse

Abstract: Synapses of the central nervous system (CNS) are specialized cell-cell junctions that mediate intercellular signal transmission from one neuron to another. The directional nature of signal relay requires that synaptic contacts are morphologically asymmetric with distinct protein components, while changes in synaptic communication during neural network formation require synapses to be plastic. Synapse morphology and plasticity require a dynamic actin cytoskeleton. Classical cadherins, which are junctional prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 37 publications
0
32
0
Order By: Relevance
“…Previous studies have demonstrated that post-synaptic b-catenin deletion in cultured hippocampal neurons alters homeostatic adaptations at the presynaptic site (Vitureira et al 2011). Therefore, as it has previously been shown that the structure and function of presynaptic and post-synaptic components of the synapse are highly coordinated (Kwiatkowski et al 2007;Vitureira et al 2011), it is possible that expression of b-catenin at the presynaptic site, in DA axon terminals, is necessary to coordinate the formation and function of post-synaptic sites in striatal medium spiny neurons.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Previous studies have demonstrated that post-synaptic b-catenin deletion in cultured hippocampal neurons alters homeostatic adaptations at the presynaptic site (Vitureira et al 2011). Therefore, as it has previously been shown that the structure and function of presynaptic and post-synaptic components of the synapse are highly coordinated (Kwiatkowski et al 2007;Vitureira et al 2011), it is possible that expression of b-catenin at the presynaptic site, in DA axon terminals, is necessary to coordinate the formation and function of post-synaptic sites in striatal medium spiny neurons.…”
Section: Discussionmentioning
confidence: 98%
“…In addition to its role in development and cell proliferation, b-catenin has been implicated in neuronal synapse regulation and remodeling by acting both pre-and post-synaptically (Kwiatkowski et al 2007). For example, previous studies have shown that genetic deletion of the gene that encodes b-catenin, Ctnnb1, in the amygdala results in impaired learning by disrupting the consolidation of memories induced by fear (Maguschak and Ressler 2008).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another rare nonsynonymous SNP was found in one patient and an affected sibling, but no other patients, so its significance could be not determined. Recently published studies suggest that genetic variation in the cadherin member FAT is involved in BD (Blair et al, 2006), and haplotypes within 22q11-linked ARVCF, a member of the catenin family that maps immediately 3' to COMT, are associated with SZ (Sanders et al, 2005); catenins interact with cadherins to modulate synaptic function (reviewed by Kwiatkowski et al, 2007).…”
Section: Discussionmentioning
confidence: 99%